1985
DOI: 10.1159/000132098
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic association between the XY chromosomes and unpaired autosomal elements as a cause of human male sterility

Abstract: Intimate association between autosomal translocation trivalents and XY bivalents at pachytene was observed in a majority of cells of two men ascertained through primary sterility and found to be heterozygous for a 14;21 Robertsonian translocation. The association, studied by light and electron microscopy of spread first spermatocytes, was between the unpaired short arms of the normal chromosomes of the translocation trivalent and the differential axes of the XY chromosomes. In a minority of cells, this contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0
8

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 24 publications
6
68
0
8
Order By: Relevance
“…These data are also in agreement with those obtained after human sperm-hamster oocyte fertilization (Table 2): indeed, Pellestor (1990) reported a majority of balanced chromosome complements (87.4%) resulting from an alternate mode of segregation in spermatozoa of a (13;15) translocation carrier. These observations corroborate with the prevalent formation of a cis configuration in the meiotic trivalent structure of ROBs (Vidal et al 1982;Luciani et al 1984;Templado et al 1984;Rosenmann et al 1985), the cis configuration leading to the predominant alternate segregation. These authors also confirm that meiotic segregation of ROBs does not occur randomly.…”
Section: Discussionsupporting
confidence: 82%
“…These data are also in agreement with those obtained after human sperm-hamster oocyte fertilization (Table 2): indeed, Pellestor (1990) reported a majority of balanced chromosome complements (87.4%) resulting from an alternate mode of segregation in spermatozoa of a (13;15) translocation carrier. These observations corroborate with the prevalent formation of a cis configuration in the meiotic trivalent structure of ROBs (Vidal et al 1982;Luciani et al 1984;Templado et al 1984;Rosenmann et al 1985), the cis configuration leading to the predominant alternate segregation. These authors also confirm that meiotic segregation of ROBs does not occur randomly.…”
Section: Discussionsupporting
confidence: 82%
“…The authors have suggested that the proximity of the autosomal segment with the X chromosome may interfere with its inactivation process by harming the germinative cell. This kind of association has often been found in infertile men with balanced Robertsonian translocation between chromosomes 13 and 14 (Luciani et al, 1984) and 14 and 21 (Rosenmann et al, 1985).…”
Section: Introductionmentioning
confidence: 71%
“…On the other hand, the translocated chromosomes would form a pairing cross during meiosis, hindering the meiotic process and leading to spermatogenic arrest [9,10], which may be another mechanism of the association between chromosome translocation and oligozoospermia.…”
Section: Discussionmentioning
confidence: 99%